Nivolumab in relapsed/refractory Hodgkin lymphoma: towards a new treatment strategy? - Cencini, Emanuele (Am J Blood Res, 2021)
Chemo-refractory Hodgkin lymphoma (HL), especially after failure of high-dose therapy and autologous stem cell transplantation (ASCT), has a very poor prognosis. Nivolumab, an anti-PD-1 monoclonal antibody, demonstrated durable responses and manageable toxicity in a significant proportion of HL patients who fail both ASCT and brentuximab vedotin. Although anti-PD-1 treatment is often well tolerated, immune-related adverse events (iAE) were frequently observed. New perspectives could be represented by treatment discontinuation in patients with prolonged response or toxicity with the possibility of a re-treatment at relapse, subsequent chemotherapy or a modification of the dose-intensity or treatment duration. The efficacy of anti-PD-1 re-treatment was demonstrated in several cases and we have successfully managed 1 case with this strategy. With the main aim of avoiding the relapse-related psychophysical stress for the patient with manageable toxicity, we have successfully administered nivolumab every 4 weeks to 3 patients in prolonged complete remission, who presented with iAE during treatment. We believe that nivolumab should not only represent a bridge to allogeneic SCT, but it may play an important role also beyond the approved indication and current standard clinical care.